Fred Kossam speaks about status of agriculture in the SBSTA 40 negotiations - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
Fred Kossam speaks about status of agriculture in the SBSTA 40 negotiations in Bonn, Germany June 2014.